An Aproach to Selectively Block Mobile Phone Communication within a Mobile Phone Restricted Area - Agyare, Michael (2025)
A thesis submitted to the Department of Electrical Engineering, Kwame Nkrumah University of Science and Technology, Kumasi in Partial fulfilment of the requirements for the award degree of MASTER OF PHILOSOPHY IN TELECOMMUNICATION ENGINEERING